Evaluation of affecting factors for conversion to open cholecystectomy in acute cholecystitis - Oymaci, Erkan; Ucar, Ahmet Deniz; Aydogan, Serdar; Sari, Erdem; Erkan, Nazif; Yildirim, Mehmet (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Laparoscopic cholecystectomy has become the gold standard for the surgical treatment of gallbladder disease. Severe inflammation makes laparoscopic dissection technically more demanding in acute cholecystitis. Conversion to open cholecystectomy due to adverse conditions is still required in some patients. Aim: To evaluate predictive risk factors associated with conversion to open cholecystectomy in acute cholecystitis. Material and methods : A retrospective analysis was performed on 165 patients who underwent a laparoscopic cholecystectomy for acute cholecystitis in our clinic. Patients who completed laparoscopic cholecystectomy and required conversion to open cholecystectomy were compared in terms of age, sex, fever, laboratory and USG findings, operation timing, complications, and duration of hospital stay. Results: There were 53 (32%) male and 112 (68%) female patients; the mean age was 52.4 ±12.5 years. Forty-six (27.9%) of the 165 patients were converted to open cholecystectomy. Male sex of the patients who underwent conversion (47.1%) was found to be statistically significant (p < 0.001). Preoperative white blood count, blood glucose and amylase values, morbidity rate, and hospital stay were raised in patients who underwent conversion, and all were found to be statistically significant (p < 0.05). Conclusions : Male sex, blood leucocyte, glucose, and raised amylase emerged as the effective factors for conversion cholecystectomy in our study. These factors should help the clinical decision-making process when planning laparoscopic cholecystectomy in acute cholecystitis. By predicting these risk factors for conversion, preoperative patient counselling can be improved.